THE EFFECT OF VIDEO RECORDING FEEDBACK ON STUDENT SPEAKING SKILL AT FIRST GRADE OF SMA N 7 MALANG - ajib amala hafi; Mutmainnah Mustofa (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
The purpose of this research is to investigate the effect of video recording feedback on student speaking skill at first grade of SMAN 7 Malang. The design of this research was experimental research with types of Quasi-Experimental research. The researcher focused on two classes, that were X MIPA 3 was 29 for experimental group, and X MIPA 4 was 28 for control group. The instruments test was five topics which were chosen by the students’ self. The researcher conducted pre-test, treatment, and post-test. The data from both pre-test and post-test was analysed using t-test analysis. The score of experimental class was significantly higher than controlled class. The result of analysing pre-test score and post-test showed that the significant level of 0.038 was less than level of significant (α) 0.05. It means that using video recording feedback was effective in improving speaking skill at first grade of SMAN 7 Malang. It can be concluded that the student who was taught using video recording feedback was better than using conventional method as it helped the students to improve their speaking performance and speaking ability, so it could improve their speaking score.